Climate Migrant Elderly Abuse and Neglect: A Study in Slums of Dhaka, Bangladesh - Karisma Amjad (Journal of Aging Research And Healthcare, 2020)
Bangladesh many older people spend their life in not only the unwell health but also in poverty which is major risk for the elderly population. This is especially true for older women, who suffer from various difficulties ensuing from prejudices to gender, widowhood and old age. Climate migrants start living in urban slums are in search of better and secure life. But urban slums located mostly in low lying environmentally hazardous area coupled with inadequate facilities like food, shelter, sanitation, health care make their life even worse. Older Women are the vulnerable groups in society in terms of climate change, movement; haphazard growth and unhealthy environment are the target group for this research. This study represents the nature and extent of elderly abuse of climate migrant urban poor women slum dwellers in Dhaka city in Bangladesh context. Besides, this paper also observe the socio-economic status of the study respondents and try to find out the self-stated reasons of elderly abuse. This study conducted both quantitative and qualitative types study on two slums of Dhaka with purposive sample survey, KII and in depth qualitative interview of selected climate migrant slum dwellers while purposive sample size of 50. Decreasing in earning capacity, inability and economic dependency, health hazard, maladjustment, changing social values have a separate role in the connection of older abuse. Planned migration, awareness program implantations against elderly abuse and secured socioeconomic factors are suggested through this paper to lessen exposure to further neglecting of elderly climate migrant women in urban slums.
Keywords: Climate migrants